2012
DOI: 10.1111/jai.12088
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of spatio-temporal variation in larval abundance of lake sturgeon (Acipenser fulvescens ) in the Rupert River (Quebec, Canada), using drift nets

Abstract: Summary The Rupert River is one of the largest tributaries on the east coast of James Bay. Lake sturgeon (Acipenser fulvescens) is present all along the main stem where several spawning grounds have been located, four of which are major spawning grounds that have been studied at km 216, 281, 290 and 362. The total number of drifting larvae was estimated with drift nets set along transverse transects at km 212, 276, and km 287 from 2007 to 2009, and at km 361 in 2008 and 2009, using a new technique, namely, a D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Less understood is the significant variation in larval success that can exist between sites on a single river or at a single sight over several years (Benson et al 2006;Kempinger 1988;LaHaye et al 1992). Nilo et al (1997), Verdon et al (2013), Shaw et al 2012, and Caroffino et al (2010a, 2010b found that year class strength is determined in the first few months of life by climate, hydrological conditions, and predation and is highly variable between years and sites. Duong et al (2011a) found that some of this variation could be explained by environmental variables, maternal effects, and spawning time.…”
Section: Larvaementioning
confidence: 98%
“…Less understood is the significant variation in larval success that can exist between sites on a single river or at a single sight over several years (Benson et al 2006;Kempinger 1988;LaHaye et al 1992). Nilo et al (1997), Verdon et al (2013), Shaw et al 2012, and Caroffino et al (2010a, 2010b found that year class strength is determined in the first few months of life by climate, hydrological conditions, and predation and is highly variable between years and sites. Duong et al (2011a) found that some of this variation could be explained by environmental variables, maternal effects, and spawning time.…”
Section: Larvaementioning
confidence: 98%
“…However, the area of available spawning habitat may be substantially reduced relative to the extent of inaccessible upstream habitat (Raspopov et al., ; Ruban and Khodorevskaya, ). Remediation at non‐tailrace locations often shows limited long‐term success due to factors such as inconsistent use by spawning adults (Khoroshko & Vlasenko, ), or the deposition of fine substrates leading to decreased egg or yolk‐sac larvae survival (Table , case studies; Veshchev et al., ). Greater attention to reach scale hydraulic conditions and their effects on spawning location and substrate will hopefully lead to improved success for remediation in non‐tailrace habitats.…”
Section: Introductionmentioning
confidence: 99%
“…This may be a function of flow as the current downstream of a dam is not as dispersed as in a natural river, but turbulence flows with high velocity emanating from turbines or sluice gates. Drifting larvae are surface‐oriented (Caroffino, Daugherty, & Sutton, ; Caroffino et al., ; Verdon et al., ) and could be flushed out of turbulent flows and settle within the first pool (i.e., close to the dam). An alternate theory could be related to the timing of drift associated with the operation of the hydroelectric facility.…”
Section: Discussionmentioning
confidence: 99%